Zoogeographical analysis of the scale insect fauna of Poland (Bollettino di zoologia agraria e bachicoltura, 2024)
A list of 137 scale insects species from Poland, belonging to 9 families is presented. The species that occur in Poland can be divided to three groups: 1) species restricted to the Palearctic region (106 species, 77.4% of the total fauna), 2) species whose range is limited to 2-3 zoogeographical regions (22 species, 16.0% of the total fauna), 3) cosmopolitan species (9 species, 6.6% of the total fauna). The Palearctic species are divided into the following subgroups: a) species widely distributed in the Palearctic region (50% species, 47.2%), b) species distributed in two subregions (31 species, 29.2%), e) species restricted only to Euro-Siberian region (25 species, 23.6%). Among the latter, there are 12 species which occur only in a few countries. A brief comment is given on each group. The ratio of species per genera was also calculated.
Keywords: Hemiptera; Coccoidea; zoogeography; Poland